PENGARUH PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT, SUPERVISI SEBAGAI VARIABEL MODERATING PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA MEDAN - Anisa Putri Salsabila; Muhammad Fahmi; Facrul Rozi; Riva Ubar Harahap (Worksheet : Jurnal Akuntansi, 2026)
This study aims to examine and analyze the influence of auditor experience on audit quality and the role of supervision as a moderating variable in Public Accounting Firms (KAP) in Medan. This is a quantitative study using an associative approach. The population in this study was all auditors working in Public Accounting Firms (KAP) in Medan, with a sample size of 83 auditors. The data collection method used a survey method by distributing questionnaires to respondents. The data analysis technique employed a quantitative approach using statistical analysis using the Automated Model Analysis (AU), Inner Model Analysis (IN), Hypothesis Testing, and Moderated Regression Analysis (MRA). Data processing in this study used SemPLS (Partial Least Squares) software. The results of the study indicate that auditor experience has a positive and significant effect on audit quality. This indicates that auditors with more work experience have a better ability to detect material misstatements and apply audit procedures appropriately. Furthermore, the results of the moderating variable test indicate that supervision does not moderate the effect of auditor experience on audit quality.